A life-threatening rare presentation of spontaneous liver tumor rupture with respiratory distress and further lifesaving management with literature review - Saba Nabavi Monfared (17269033) (2021)
A 54 year old Bangladeshi gentleman, with recently diagnosed hepatocellular carcinoma due to chronic hepatitis B infection with peritoneal metastasis presented to the emergency department with complain of abdominal pain and gradual distention over 7–10 days. There was no associated fever, nausea, hematochezia or any difficulty in passing stool. Blood pressure on presentation was 110/60 mmHg with heart rate of 110/min, respiratory rate of 28/min and normal oxygen (O2) saturation at room air. On clinical examination, the patient was distressed due to tense abdomen with slit like umbilicus. On clinical examination, the patient was cachectic looking and was having jaundice and pallor. Flanks were full and there was positive fluid thrill on clinical examination. There were no other stigmata of chronic liver disease. Urgent bed side point of care ultrasound (POCUS) was remarkable for massive ascites. Urgent USG guided abdominal paracentesis revealed hemorrhagic ascites. Next day the patient became hypotensive and hemoglobin dropped to 2 gm/dl from the initial presentation. Other Information Published in: Visual Journal of Emergency Medicine License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.visj.2021.101146